Binder, preparation method thereof and application of binder in lithium ion capacitor
By preparing the adhesive rich in specific groups, the problem of insufficient compatibility of existing adhesives and carbon materials interfaces, improved the stability of the electrolyte, reduced gas production, improved the safety of lithium -ion capacitors Sex and performance.
Patent Information
- Application Number
- CN202411929558.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The lack of interface compatibility between the existing binders and negative electrode carbon materials, which makes it difficult for carbon materials to wet and disperse in the water system, and the irreversible decomposition of the electrolyte results in large gas production, which affects the rate performance and cycle life of the lithium-ion capacitor.
The adhesive is prepared by combining sodium lignosulfonate rich in methoxy, hydroxyl, carbonyl and sulfonic acid groups with polyacrylamide containing amide groups through hydrogen bonding to form a bond with the characteristics of multiple hydrophobic groups and multiple hydrophilic groups. agent to improve the interfacial compatibility of carbon materials and the stability of the electrolyte.
By improving the wetting and dispersion of carbon materials, the irreversible decomposition of the electrolyte is reduced, the amount of gas produced is reduced, and the safety and performance stability of lithium-ion capacitors are improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion capacitors, and in particular to a binder and a preparation method thereof and application in lithium ion capacitors. Background Art
[0002] As a new type of electrochemical energy storage device, lithium-ion capacitors have an energy density between lithium-ion batteries and supercapacitors, and have the characteristics of high capacity and long cycle life. The negative electrode active material is a key factor affecting the side reactions and rate performance of lithium-ion capacitors. Carbon materials are generally used as negative electrode active materials in commercial lithium-ion capacitors. Carbon materials themselves have the characteristics of a certain interlayer spacing, porosity, large specific surface area, and a variety of functional groups on the surface, which makes lithium-ion capacitors have high rate and long cycle life, thus gaining wide application. However, at the same time, due to the above structural characteristics, carbon materials are difficult to disperse in aqueous systems on the one hand, and on the other hand, the contact between the electrolyte and the surface of the carbon material causes irreversible consumption of the electrolyte, aggravated side reactions, and large gas production. The above two shortcomings will affect the product rate performance and cycle life. At present, the existing technology improves the above shortcomings by optimizing electrolytes and binders.
[0003] Among them, the binder has special chemical and physical properties and plays an important role in the production of negative electrodes. Currently common binders such as polyacrylic acid (PAA), polyvinylidene fluoride (PVDF) and sodium carboxymethyl cellulose (CMC) are polymer materials with high elasticity and flexibility. However, there are still the following problems: the types and numbers of polar groups carried by these polymer binders are small and lack interfacial compatibility with carbon materials, which cannot effectively alleviate the serious agglomeration of negative electrode carbon materials and the gas production caused by irreversible decomposition of electrolytes. Summary of the invention
[0004] The purpose of the present invention is to provide a binder and a preparation method thereof and application in lithium ion capacitors, so as to solve the problems of lack of interfacial compatibility between the existing binder and the negative electrode carbon material and large gas production caused by irreversible decomposition of the electrolyte, which is beneficial to the wetting and dispersion of the carbon material in the aqueous system, and the formed carbon particles with smaller particle size are in more complete contact with the conductive material, while greatly reducing the irreversible decomposition of the electrolyte, thereby reducing the gas production, which is conducive to the safety of the lithium ion capacitor.
[0005] The technical solution of the present invention is: A binder, the technical main points of which are: It is obtained by hydrogen bonding sodium lignin sulfonate rich in methoxy, hydroxyl, carbonyl and sulfonic acid groups with polyacrylamide containing amide groups. The reaction process is as follows: Among them, a is the molecular structure formula of polyacrylamide, b is the molecular structure formula of sodium lignin sulfonate, and c is the assembly diagram of the binder.
[0006] The above-mentioned binder is composed of the following components by weight: Sodium lignin sulfonate: polyacrylamide = (7-10): (0.7-1); the sulfonation degree of the sodium lignin sulfonate is 1.5-2.5 mmol / g, the purity is 97%-99%, and the relative molecular weight is 5000-10000 Dalton; the polyacrylamide is cationic polyacrylamide, anionic polyacrylamide or nonionic polyacrylamide, and the molecular weight is 1×10 6 ~1×10 7 Dalton, purity ≥99%.
[0007] A method for preparing the above-mentioned adhesive comprises the following steps: Step 1, adding sodium lignin sulfonate into a deionized water solution, stirring to fully dissolve it, to form an LS solution; Step 2, adding polyacrylamide PAM to the LS solution, initially stirring to fully dissolve it, and then heating and stirring to form LS-PAM gel; Step 3: spray-dry, dry, grind and sieve the obtained LS-PAM gel to obtain LS-PAM particles, namely binder A.
[0008] The preparation method of the above-mentioned binder, in step 1, the stirring speed is 100-500 rpm, the stirring temperature is 10-30°C, and the stirring time is 0.5-2 hours; in step 2, the stirring speed of the initial stirring is 600-1000 rpm, the stirring temperature is 10-30°C, and the stirring time is 0.5-2 hours; the stirring speed of the heated stirring is 600-1000 rpm, the stirring temperature is 30-60°C, and the stirring time is 1-4 hours; the LS-PAM The solid content of the gel is 20% to 30%; in step 3, the nozzle diameter for spray drying is 0.5 to 2.0 mm, the hot air temperature is 80 to 150° C., and the peristaltic pump speed is 500 to 1000 ml / h; the drying temperature is 80 to 110° C., and the drying time is 2 to 5 hours; the grinding speed is 100 to 150 rpm, and the grinding time is 0.2 to 1 hour; the sieving is through a nylon sieve of 80 to 120 meshes; the water content of the LS-PAM particles is ≤5%, and the particle size is ≤180 μm.
[0009] An application of the above-mentioned binder in a lithium ion capacitor, the technical key point of which is that the negative electrode plate of the lithium ion capacitor is composed of the following components by solid mass percentage: 4% to 15% conductive agent, 1% to 8% binder A, 1% to 7% binder B, and 70% to 94% carbon material; The conductive agent is one or more combinations of Super P, Ketjen black, acetylene black, graphene, carbon nanotubes and carbon fibers; The binder A is obtained by hydrogen bonding sodium lignin sulfonate rich in methoxy, hydroxyl, carbonyl and sulfonic acid groups with polyacrylamide containing amide groups; The B binder is one or more combinations of acrylonitrile multi-polymer emulsion, styrene-butadiene rubber emulsion, polytetrafluoroethylene emulsion, and polyacrylate emulsion; The carbon material is one or more combinations of graphite, mesophase carbon microspheres, hard carbon and soft carbon.
[0010] The application of the above binder in lithium ion capacitors, the method for making the negative electrode sheet comprises the following steps: Step 1, add binder A into deionized water and stir to fully dissolve it; Step 2, adding the carbon material to the solution formed in step 1, and stirring to mix evenly; Step 3, adding the conductive agent to the slurry formed in step 2, and stirring to mix evenly; Step 4: Add the Binder B to the slurry formed in step 3, and stir to mix evenly to meet the coating requirements; Step 5: evenly coat the slurry formed in step 4 on the negative electrode current collector, dry, roll and cut to obtain the negative electrode sheet.
[0011] The application of the above binder in lithium ion capacitors, in step 1, the stirring speed is 400-1000 rpm, the stirring time is 1-5 hours, and the stirring temperature is 10-30°C; in step 2, the stirring speed is 800-3000 rpm, the stirring time is 1-5 hours, and the stirring temperature is 10-30°C; in step 3, the stirring speed is 800-3000 rpm, the stirring time is 1-20 hours, and the stirring temperature is 10-30°C; in step 4, the stirring speed is 200-1000 rpm, the stirring time is 1-5 hours, and the stirring temperature is 10-30°C. The slurry fineness that meets the coating requirements is 20-100 μm, the viscosity is 500-10000 mPa / s, and the solid content is 30%-70%.
[0012] Application of the above binder in lithium ion capacitors: In step 5, the negative electrode current collector is a microporous copper foil with a thickness of 8 to 20 μm and a through-hole density of 500 to 1000 per cm 2 The through hole diameter is 1 to 30 μm; the drying temperature is 80 to 130° C., the drying time is 5 to 30 minutes; the rolling pressure is 5 to 20 MPa, and the number of rolling times is 1 to 3 times.
[0013] The above-mentioned binder is used in a lithium ion capacitor, which includes a capacitor housing, a laminated battery cell placed inside the capacitor housing, and an electrolyte. The laminated battery cell includes a negative electrode sheet, a separator, and a positive electrode sheet that are alternately stacked in a cycle. Lithium auxiliary electrodes are respectively arranged on both sides of the outermost negative electrode sheet. The lithium auxiliary electrodes are formed by compacting lithium sheets or lithium powder by rolling and filling them on the negative electrode current collector.
[0014] The application of the above binder in a lithium ion capacitor, the preparation method of the lithium ion capacitor comprises the following steps: Step 1: The negative electrode sheet, the separator and the positive electrode sheet are alternately stacked in a cycle, and the lithium auxiliary electrodes are placed on both sides of the outermost negative electrode sheet to make a stacked battery cell; Step 2, placing the laminated battery core into a capacitor housing for sealing, wherein the capacitor housing is an aluminum-plastic film; Step 3: injecting electrolyte into the capacitor housing, sealing it, and performing chemical formation to obtain a lithium ion capacitor.
[0015] The beneficial effects of the present invention are: The binder (LS-PAM) of the present invention has the characteristics of multiple hydrophobic groups and multiple hydrophilic groups, which can be combined with the surface of the carbon material, which is more conducive to the wetting and dispersion of the carbon material in the water system. The carbon particles with smaller particle size formed can contact the conductive material more fully. At the same time, LS-PAM forms multiple hydrophilic groups on the surface of the carbon material, such as amide groups and sulfonic acid groups, which can weaken the Li + The interaction between Li + The desolvation performance of Li + The transmission rate of Li + The interaction between Li and organic solvent molecules is reduced, and fewer organic solvent molecules can follow Li + Reaching the surface of the carbon material electrode, thereby reducing its irreversible decomposition, accompanied by less gas generation, contributes to the safety of lithium-ion capacitors. DETAILED DESCRIPTION
[0016] Example 1, a binder and a preparation method thereof and application in a lithium ion capacitor.
[0017] (1) Preparation of binder: Weigh 240 g of sodium lignin sulfonate with a sulfonation degree of 1.5 mmol / g, a purity of 97%, and a relative molecular weight of 5000-10000 Daltons, add it to 1000 g of deionized water solution, and stir at 10°C and 100 rpm for 0.5 hours to fully dissolve it to form an LS solution. 6 ~1×10 7Dalton, 34g of anionic polyacrylamide with a purity of ≥99% was added to the LS solution, stirred at 10°C and 600 rpm for 0.5 hours to fully dissolve it, then heated to 30°C and stirred at 600 rpm for 1 hour to form LS-PAM gel. The obtained LS-PAM gel was spray-dried with a nozzle diameter of 0.5mm, a hot air temperature of 80°C, and a peristaltic pump speed of 500ml / h. The collected LS-PAM coarse particles were dried at 80°C for 2 hours. The dried LS-PAM coarse particles were ground at 100 rpm for 0.2 hours. The ground LS-PAM fine particles were sieved through an 80-mesh nylon screen to obtain the final LS-PAM particles, that is, the A binder.
[0018] (2) Preparation of negative electrode sheet: Add 1% of A binder to deionized water, stir at 10℃, 400 rpm for 5 hours to fully dissolve it. Add 70% hard carbon, 15% graphite and 9% mesophase carbon microspheres, stir at 10℃, 800 rpm for 5 hours to disperse it evenly. Add 4% Super P, stir at 10℃, 800 rpm for 20 hours to disperse it evenly. Add 1% styrene-butadiene rubber latex, stir at 10℃, 200 rpm for 5 hours to disperse it evenly.
[0019] The negative electrode slurry is evenly coated on a plate with a thickness of 8 μm and a through-hole density of 1000 / cm 2 , on a microporous copper foil with a through hole diameter of 1 μm, dried at 80°C for 30 minutes. Rolled once with a roller pressure of 20 MPa.
[0020] (3) Preparation of lithium ion capacitors: The negative electrode sheet is cut into a set size, and is stacked with the separator and the positive electrode sheet in a loop, and then a lithium auxiliary electrode is set to form a laminated battery cell. The laminated battery cell is wrapped and sealed with an aluminum-plastic film to form a capacitor shell. The electrolyte is injected into the capacitor shell, sealed, and formed to prepare a lithium ion capacitor example 1.
[0021] Example 2, a binder and a preparation method thereof and application in a lithium ion capacitor.
[0022] (1) Preparation of binder: Weigh 250 g of sodium lignin sulfonate with a sulfonation degree of 2.0 mmol / g, a purity of 98%, and a relative molecular weight of 5000-10000 Daltons, add it to 1000 g of deionized water solution, stir at 20°C and 300 rpm for 1.5 hours to fully dissolve it to form an LS solution. 6 ~1×10 7Dalton, 25g of cationic polyacrylamide with a purity of ≥99% is added to the LS solution, stirred at 20°C and 800 rpm for 1.5 hours to fully dissolve it, then heated to 45°C and stirred at 800 rpm for 2.5 hours to form LS-PAM gel. The obtained LS-PAM gel is spray-dried with a nozzle diameter of 1.0mm, a hot air temperature of 110°C, and a peristaltic pump speed of 750ml / h. The collected LS-PAM coarse particles are dried at 100°C for 3 hours. The dried LS-PAM coarse particles are ground at 120 rpm for 0.5 hours. The ground LS-PAM fine particles are screened through a 100-mesh nylon sieve to obtain the final LS-PAM particles, that is, the A binder.
[0023] (2) Preparation of negative electrode sheet: Add 4% of A binder to deionized water, stir at 25℃, 600 rpm for 3 hours to fully dissolve it. Add 70% hard carbon and 15% graphite, stir at 25℃, 2000 rpm for 3 hours to disperse it evenly. Add 4% Super P, 1% Ketjen black and 2% graphene, stir at 25℃, 2000 rpm for 12 hours to disperse it evenly. Add 2% styrene-butadiene rubber latex and 2% acrylonitrile multipolymer latex, stir at 25℃, 600 rpm for 3 hours to disperse it evenly.
[0024] The negative electrode slurry is evenly coated on a surface with a thickness of 15 μm and a through-hole density of 800 per cm 2 , on a microporous copper foil with a through hole diameter of 15μm, dried at 110℃ for 20 minutes. Rolled twice with a roller pressure of 10Mpa.
[0025] (3) Preparation of lithium ion capacitors: The negative electrode sheet is cut into a set size, and is stacked with the separator and the positive electrode sheet in a loop, and then a lithium auxiliary electrode is provided to form a laminated battery cell. The laminated battery cell is wrapped and sealed with an aluminum-plastic film to form a capacitor housing. The electrolyte is injected into the capacitor housing, sealed, and formed to prepare a lithium ion capacitor example 2.
[0026] Example 3, a binder and a preparation method thereof and application in a lithium ion capacitor.
[0027] (1) Preparation of binder: Weigh 256 g of sodium lignin sulfonate with a sulfonation degree of 2.5 mmol / g, a purity of 99%, and a relative molecular weight of 5000-10000 Daltons, add it to 1000 g of deionized water solution, and stir at 30°C and 500 rpm for 2 hours to fully dissolve it to form an LS solution. 6 ~1×10 7Dalton, 19g of nonionic polyacrylamide with a purity of ≥99% was added to the LS solution, stirred at 30°C and 1000 rpm for 2 hours to fully dissolve it, then heated to 60°C and stirred at 1000 rpm for 4 hours to form LS-PAM gel. The obtained LS-PAM gel was spray-dried with a nozzle diameter of 2.0mm, a hot air temperature of 150°C, and a peristaltic pump speed of 1000ml / h. The collected LS-PAM coarse particles were dried at 110°C for 5 hours. The dried LS-PAM coarse particles were ground at 150 rpm for 1 hour. The ground LS-PAM fine particles were screened with a 120-mesh nylon screen to obtain the final LS-PAM particles, that is, the A binder.
[0028] (2) Preparation of negative electrode sheet: Add 8% of A binder to deionized water, stir at 30℃, 1000 rpm for 1 hour to fully dissolve it. Add 70% hard carbon, stir at 30℃, 3000 rpm for 1 hour to disperse it evenly. Add 6% Super P, 1% Ketjen black, 2% graphene and 6% carbon nanotubes, stir at 30℃, 3000 rpm for 1 hour to disperse it evenly. Add 3% styrene-butadiene rubber latex, 3% acrylonitrile multipolymer latex and 1% polyacrylate latex, stir at 30℃, 1000 rpm for 1 hour to disperse it evenly.
[0029] The negative electrode slurry is evenly coated on a surface with a thickness of 20 μm and a through-hole density of 500 / cm 2 , on a microporous copper foil with a through hole diameter of 30μm, dried at 130℃ for 5 minutes. Rolled 3 times with a roller pressure of 5Mpa.
[0030] (3) Preparation of lithium ion capacitors: The negative electrode sheet is cut into a set size, and is stacked with the separator and the positive electrode sheet in a loop, and then a lithium auxiliary electrode is set to form a laminated battery cell. The laminated battery cell is wrapped and sealed with an aluminum-plastic film to form a capacitor shell. The electrolyte is injected into the capacitor shell, sealed, and formed to prepare a lithium ion capacitor example 3.
[0031] In contrast, the prior art prepares negative electrode plates and lithium ion capacitors.
[0032] (1) Preparation of negative electrode sheet: Add 2% sodium carboxymethyl cellulose (CMC) to deionized water, stir at 25°C, 600 rpm for 3 hours to fully dissolve it. Add 87% hard carbon, stir at 25°C, 2000 rpm for 3 hours to disperse it evenly. Add 7% Super P, stir at 25°C, 2000 rpm for 12 hours to disperse it evenly. Add 4% styrene-butadiene rubber latex, stir at 25°C, 600 rpm for 3 hours to disperse it evenly.
[0033] The negative electrode slurry is evenly coated on a surface with a thickness of 15 μm and a through-hole density of 1000 / cm 2 , on a microporous copper foil with a through hole diameter of 10μm, dried at 110℃ for 20 minutes. Rolled twice with a roller pressure of 5Mpa.
[0034] (2) Preparation of lithium ion capacitors: The negative electrode sheet is cut into a set size and stacked with the separator and the positive electrode sheet in a loop, and then a lithium auxiliary electrode is set to form a laminated battery cell. The laminated battery cell is wrapped and sealed with an aluminum-plastic film to form a capacitor shell. The electrolyte is injected into the capacitor shell, sealed, and formed to prepare a lithium-ion capacitor control sample.
[0035] Table 1 Test results of the adhesive preparation described in Examples 1 to 3
[0036] Table 2 Comparative Examples and Test Results of Negative Electrode Slurry Preparation of Examples 1 to 3
[0037] Table 3 Comparative Example and Examples 1 to 3 Negative Electrode Sheet Preparation Test Results
[0038] Table 4 Test results of lithium ion capacitors made of binder negative electrode sheets
[0039] The embodiments of the present invention are described in detail above, but the contents described are only preferred embodiments of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.
Claims
1. A binder, characterized in that: It is obtained by hydrogen bonding sodium lignin sulfonate rich in methoxy, hydroxyl, carbonyl and sulfonic acid groups with polyacrylamide containing amide groups. The reaction process is as follows: Wherein, a is the molecular structure formula of polyacrylamide, b is the molecular structure formula of sodium lignin sulfonate, and c is the assembly diagram of the binder.
2. The adhesive according to claim 1, characterized in that It is composed of the following components by weight: Sodium lignin sulfonate: polyacrylamide = (7-10): (0.7-1); the sulfonation degree of the sodium lignin sulfonate is 1.5-2.5 mmol / g, the purity is 97%-99%, and the relative molecular weight is 5000-10000 Dalton; the polyacrylamide is cationic polyacrylamide, anionic polyacrylamide or nonionic polyacrylamide, and the molecular weight is 1×10 6 ~1×10 7 Dalton, purity ≥99%.
3. A method for preparing the adhesive according to claim 1 or 2, characterized in that: The steps include: Step 1, adding sodium lignin sulfonate into a deionized water solution, stirring to fully dissolve it, to form an LS solution; Step 2, adding polyacrylamide PAM to the LS solution, initially stirring to fully dissolve it, and then heating and stirring to form LS-PAM gel; Step 3: spray-dry, dry, grind and sieve the obtained LS-PAM gel to obtain LS-PAM particles, which are the binder.
4. The method for preparing the adhesive according to claim 3, characterized in that: In step 1, the stirring speed is 100 to 500 rpm, the stirring temperature is 10 to 30°C, and the stirring time is 0.5 to 2 hours; in step 2, the stirring speed of the initial stirring is 600 to 1000 rpm, the stirring temperature is 10 to 30°C, and the stirring time is 0.5 to 2 hours; the stirring speed of the heated stirring is 600 to 1000 rpm, the stirring temperature is 30 to 60°C, and the stirring time is 1 to 4 hours; the solid content of the LS-PAM gel is is 20% to 30%; in step 3, the nozzle diameter for spray drying is 0.5 to 2.0 mm, the hot air temperature is 80 to 150°C, and the peristaltic pump speed is 500 to 1000 ml / h; the drying temperature is 80 to 110°C, and the drying time is 2 to 5 hours; the grinding speed is 100 to 150 rpm, and the grinding time is 0.2 to 1 hour; the sieving is through a nylon sieve of 80 to 120 meshes; the water content of the LS-PAM particles is ≤5%, and the particle size is ≤180 μm.
5. Use of the binder according to claim 1 or 2 in a lithium ion capacitor, characterized in that: The negative electrode plate of the lithium ion capacitor is composed of the following components in terms of solid mass percentage: 4% to 15% conductive agent, 1% to 8% A binder, 1% to 7% B binder, and 70% to 94% carbon material; The conductive agent is one or more combinations of Super P, Ketjen black, acetylene black, graphene, carbon nanotubes and carbon fibers; The binder A is obtained by hydrogen bonding sodium lignin sulfonate rich in methoxy, hydroxyl, carbonyl and sulfonic acid groups with polyacrylamide containing amide groups; The B binder is one or more combinations of acrylonitrile multi-polymer emulsion, styrene-butadiene rubber emulsion, polytetrafluoroethylene emulsion, and polyacrylate emulsion; The carbon material is one or more combinations of graphite, mesophase carbon microspheres, hard carbon and soft carbon.
6. Use of the binder according to claim 5 in a lithium ion capacitor, characterized in that: The method for manufacturing the negative electrode sheet comprises the following steps: Step 1, add binder A into deionized water and stir to fully dissolve it; Step 2, adding the carbon material to the solution formed in step 1, and stirring to mix evenly; Step 3, adding the conductive agent to the slurry formed in step 2, and stirring to mix evenly; Step 4: Add the Binder B to the slurry formed in step 3, and stir to mix evenly to meet the coating requirements; Step 5: evenly coat the slurry formed in step 4 on the negative electrode current collector, dry, roll and cut to obtain the negative electrode sheet.
7. Use of the binder according to claim 6 in a lithium ion capacitor, characterized in that: In step 1, the stirring speed is 400-1000 rpm, the stirring time is 1-5 hours, and the stirring temperature is 10-30°C; in step 2, the stirring speed is 800-3000 rpm, the stirring time is 1-5 hours, and the stirring temperature is 10-30°C; in step 3, the stirring speed is 800-3000 rpm, the stirring time is 1-20 hours, and the stirring temperature is 10-30°C; in step 4, the stirring speed is 200-1000 rpm, the stirring time is 1-5 hours, and the stirring temperature is 10-30°C. The slurry fineness that meets the coating requirements is 20-100 μm, the viscosity is 500-10000 mPa / s, and the solid content is 30%-70%.
8. Use of the binder according to claim 6 in a lithium ion capacitor, characterized in that: In step 5, the negative electrode current collector is a microporous copper foil with a thickness of 8 to 20 μm and a through-hole density of 500 to 1000 per cm 2 The through hole diameter is 1 to 30 μm; the drying temperature is 80 to 130° C., the drying time is 5 to 30 minutes; the rolling pressure is 5 to 20 MPa, and the number of rolling times is 1 to 3 times.
9. Use of the binder according to claim 5 in a lithium ion capacitor, characterized in that: The lithium ion capacitor comprises a capacitor housing, a laminated battery cell and an electrolyte disposed inside the capacitor housing. The laminated battery cell comprises a negative electrode sheet, a separator and a positive electrode sheet which are alternately stacked in a cycle. Lithium auxiliary electrodes are respectively arranged on both sides of the outermost negative electrode sheet. The lithium auxiliary electrodes are formed by compacting lithium sheets or lithium powder by rolling and filling them on a negative electrode current collector.
10. Use of the binder according to claim 9 in a lithium ion capacitor, characterized in that: The preparation method of the lithium ion capacitor comprises the following steps: Step 1: The negative electrode sheet, the separator and the positive electrode sheet are alternately stacked in a cycle, and the lithium auxiliary electrodes are placed on both sides of the outermost negative electrode sheet to make a stacked battery cell; Step 2, placing the laminated battery core into a capacitor housing for sealing, wherein the capacitor housing is an aluminum-plastic film; Step 3: injecting electrolyte into the capacitor housing, sealing it, and performing chemical formation to obtain a lithium ion capacitor.
Citation Information
Patent Citations
Lithium ion capacitor negative pole piece and preparation method thereof
CN113593920A
Method for bonding hydrogels
WO2015076205A1